Sistem Informasi Kehadiran Guru dan Jadwal Pelajaran Berbasis SMS Gateway - Achmad Baijuri (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2019)
Al-Falah Middle School is a Secondary Education level led by Lora Ahmad Musaddad Son of the First Caregiver of Al Falah Jangkar Pesantren. The education applied by this institution is the Modern Salaf, besides being taught religious education, it also teaches general education such as junior high school. Junior high school teachers often when having a teaching schedule on certain days forget about their teaching schedule so they need to be reminded by individual officers through sms or social media. Apart from that, the teacher sometimes forgets to list the attendance of teachers in the office every day. So that this makes it difficult for recap attendants at the end of each month. Therefore, this study aims to overcome these problems so as to facilitate and assist officers in carrying out their duties effectively and efficiently by designing teacher attendance information systems and getway based lesson schedules using the waterfall method in system development. The results of this study indicate that the information system designed is really helpful for schools, especially teaching hours reminders and teacher attendance recap. Keywords : Information System, Present Teacher,Schedule leason, Sms Gateway